106k views
1 vote
Complete the recursive formula of the arithmetic sequence 12, 10, 8, 6,...

b(1)=

b(n) = b(n − 1)+

User Syperus
by
4.7k points

1 Answer

7 votes

Answer:

b(n) = b(n - 1) -2

Explanation:

b(1) = first term = 12

b(n) = b(n - 1) + (-2)

b(n -1) is the term before the nth term

b(n) = b(n - 1) + (-2)

If n = 2

b(1) = 12

b(2) = b(2 - 1) + (-2)

b(2) = 12 - 2 = 10

If n = 3

b(3) = b(2) - 2

b(3) = 10 - 2 = 8

if n = 4

b(4) = b(3) - 2

b(3) = 8 - 2 = 6

If n = 5

b(5) = b(4) - 2

b(3) = 6 - 2 = 4

User Golu
by
4.8k points